Blocking the CD38/cADPR pathway plays a double-edged role in LPS stimulated microglia. (11th October 2017) - Wang, Yi-Min; Liu, Zhi-Yong; Ai, Yu-Hang; Zhang, Li-Na; Zou, Yu; Peng, Qian-Yi
Highlights: The CD38/cADPR pathway was activated in LPS-stimulated BV2 cells. Blocking this pathway reduced intracellular Ca 2+, NO and cytokines production. CD38 knockdown exerts a double-edged effect on apoptosis and NO production. Abstract: Whether the CD38/cyclic ADP-ribose (cADPR) pathway plays a protective or detrimental role in neuroinflammation remains controversial. This study aimed to determine the role of CD38 in neuroinflammation using lipopolysaccharide (LPS)-stimulated BV2 microglial cells and co-cultured Neuro-2a (N2a) cells. In monoculture experiments, BV2 cells were divided into control, CD38 interference (CD38Ri), negative control (NC), LPS, CD38Ri + LPS, NC + LPS and 8-Br-cADPR + LPS groups. In co-culture experiments, N2a cells were co-cultured with BV2 cells for 48 h. Nicotinamide adenine dinucleotide (NAD + ), cADPR and intracellular Ca 2+ levels and CD38 expression increased significantly in LPS-stimulated BV2 cells. CD38 knockdown or 8-Br-cADPR treatment significantly reduced NAD +, cADPR and intracellular Ca 2+ levels. CD38 knockdown increased iNOS and NO levels in BV2 cells without LPS treatment; however, CD38 knockdown or 8-Br-cADPR treatment reduced iNOS and NO levels in BV2 cells with LPS treatment. CD38 knockdown increased the ratio of TUNEL-positive cells and cleaved Caspase 3/Caspase 3 ratio, and decreased the Bcl-2/Bax ratio in BV2 cells without LPS treatment; however, CD38 knockdown reduced the TUNEL positivity in BV2 cells with LPS treatment. CD38 knockdown or 8-Br-cADPR inhibited TNF-α, IL-6 (interleukin-6) and IL-1β levels in LPS-stimulated BV2 cells. Co-culture with CD38 knockdown or 8-Br-cADPR-treated BV2 cells did not influence apoptosis or iNOS expression in N2a cells. In conclusion, our results indicate that blocking the CD38/cADPR pathway reduces intracellular Ca 2+, NO and the secretion of proinflammatory cytokines. CD38 knockdown exerted a detrimental effect in apoptosis and NO production in normal microglia, but played a protective role in apoptosis and NO production in LPS-stimulated microglia.